The Calcineurin Inhibitor Tacrolimus as a New Therapy in Severe Cherubism. (May 2015) - Kadlub, Natacha; Vazquez, Marie‐Paule; Galmiche, Louise; L'Herminé, Aurore Coulomb; Dainese, Linda; Ulinski, Tim; Fauroux, Brigitte; Pavlov, Ioana; Badoual, Cécile; Marlin, Sandrine; Deckert, Marcel; Leboulanger, Nicolas; et al.
ABSTRACT Cherubism is a rare genetic disorder characterized by extensive growth of a bilateral granuloma of the jaws, resulting in facial disfigurement. Cherubism is caused by gain‐of‐function mutations in the SH3BP2 gene, leading to overactivation of nuclear factor of activated T cells, cytoplasmic 1 (NFATc1)‐dependent osteoclastogenesis. Recent findings in human and mouse cherubism have suggested that calcineurin inhibitors might be drug candidates in cherubism medical treatment. A 4‐year‐old boy with aggressive cherubism was treated with the calcineurin inhibitor tacrolimus for 1 year, and clinical, radiological, and molecular data were obtained. Immunohistologic analysis was performed to compare preoperative and postoperative NFATc1 staining and tartrate resistant acid phosphatase (TRAP) activity. Real‐time PCR was performed to analyze the relative expression levels of OPG and RANKL. After tacrolimus therapy, the patient showed significant clinical improvement, including stabilization of jaw size and intraosseous osteogenesis. Immunohistologic analyses on granuloma showed that tacrolimus caused a significant reduction in the number of TRAP‐positive osteoclasts and NFATc1 nuclear staining in multinucleated giant cells. Molecular analysis showed that tacrolimus treatment also resulted in increased OPG expression. We present the first case of effective medical therapy in cherubism. Tacrolimus enhanced bone formation by stimulating osteogenesis and inhibiting osteoclastogenesis. © 2014 American Society for Bone and Mineral Research.